Analisa Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung Perpustakaan - Sari, Mirajtannia Perwita; Sulistiowati, Sulistiowati; lemantara, julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
Analysis of the influence of the quality of the service of library visitors Satisfaction is much needed in the analysis of improvements to existing questionnaires in Badan Perpustakan dan Kearsipan Provinsi Jawa Timur.Problems in Badan Perpustakan dan Kearsipan Provinsi Jawa Timur is a questionnaire distributed by the Badan Perpustakan dan Kearsipan Provinsi Jawa Timur is still less effective because of the questions that are listed in the questionnaire is still not able to reflect the quality of service in compliance with UU No. 40 Year 2007 regarding the library, so it is still said to be yet can yield measurements better service quality. In addition, the library felt difficulty in knowing what factors can affect the quality of service. Doing so will result in the parties having difficulty in performing the management improvement of the service quality of the library.The solution of the above problems is to improve the content of the questionnaire based on standards used by the library.The analysis provides information in the form of the result of the processing of the questionnaires in the form of information service quality dimensions/factors that impact customer satisfaction. Analysis of results of processing of the questionnaires is the target that will serve the purpose of achieving the level of quality of the existing information systems. Keywords: Questionnaires, Service Quality, Customer Satisfaction, Standard.